Pengaruh Suhu Pengeringan terhadap Kualitas dan Karakteristik Enkapsulat Minyak Sawit Merah - Sri Wahyuni; Nina Veronika (Jurnal Sains dan Ilmu Terapan, 2025)
Red palm oil is rich in carotene, particularly beta-carotene, which is a provitamin A, making it an excellent supplement for boosting immunity. However, carotene is highly sensitive to heat and oxidation, which can reduce its efficacy. To protect carotene levels, encapsulation technology is employed, which shields the active ingredients in red palm oil, preserving product stability and prolonging shelf life. This study aimed to investigate the encapsulation process of red palm oil, the impact of drying temperature on the quality of the encapsulated product, and the characteristics of the resulting encapsulates. The research involved raw material preparation, encapsulation, and characterization of the encapsulated red palm oil. The drying temperatures tested were 40°C, 50°C, and 60°C. The findings revealed that drying temperature significantly influenced the quality of the red palm oil encapsulates. The best encapsulate characteristics were obtained at 40°C, with the highest carotene content of 233.09 ppm and solubility of 55.57%.